1989
DOI: 10.1203/00006450-198911000-00022
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Marginal Maternal Zinc Deficiency on Pregnancy Outcome and Infant Zinc Status in Rhesus Monkeys

Abstract: ABSTRACT. To investigate the effects of marginal zinc deficiency on early development, rhesus monkeys were fed a diet marginally deficient in zinc (M, 4 pglg) throughout pregnancy and during the first month of lactation. Despite the low concentration of zinc in the diet, M dams did not develop overt signs of zinc deficiency. However, compared to control dams fed diets adequate in zinc (C; 100 pg Zn/ g), M dams showed a low response to the mitogens concanavalin A and phytohemagglutinin. Pregnancy outcome was si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 31 publications
3
6
0
Order By: Relevance
“…Our results show that parental zinc deficiency causes their progeny to be compromised in zinc status and have alternations in expression of MTF-1 and specific zinc transporters. This is consistent with results in other model organisms where maternal zinc deficiency was associated with lower amounts of zinc in their offspring’s liver or plasma [57, 62, 63]. Also, given MTF-1’s important role in regulating metallothioneins and metal homeostasis in relationship to heavy metal exposure, it is possible that zinc deficiency, either in the parent or the embryo, may cause embryos to be more sensitive to toxic metals.…”
Section: Discussionsupporting
confidence: 89%
“…Our results show that parental zinc deficiency causes their progeny to be compromised in zinc status and have alternations in expression of MTF-1 and specific zinc transporters. This is consistent with results in other model organisms where maternal zinc deficiency was associated with lower amounts of zinc in their offspring’s liver or plasma [57, 62, 63]. Also, given MTF-1’s important role in regulating metallothioneins and metal homeostasis in relationship to heavy metal exposure, it is possible that zinc deficiency, either in the parent or the embryo, may cause embryos to be more sensitive to toxic metals.…”
Section: Discussionsupporting
confidence: 89%
“…In rats, deprivation of zinc during pregnancy reduces their pups' hepatic zincmetallothionein content and degradation of these complexes is accelerated (40). Similar phenomena have been noted in the rhesus monkey neonate (41).…”
Section: Fetal and Neonatal Metabolismsupporting
confidence: 59%
“…These findings may reflect glucocorticoid-mediated changes in the number or function of lymphocyte precursors (151)(152)(153)(154). Altered lymphocyte counts or function have also been reported in the animal literature regarding in utero exposure to nutrient deficiencies (337)(338)(339). One recent study indicated that fetal exposure to vitamin A deficiency can affect early progenitors, resulting in smaller B1a and B1b lymphocyte populations (212).…”
Section: Early Lymphopoiesismentioning
confidence: 85%